The Possibility to Apply Effectuation and Causation Concepts at National Scope - Karpetc, Olga Viktorovna; Iurchenko, Ekaterina Sergeevna (Economy of Regions, 2017)
The article presents a new approach to the efficiency analysis of state macroeconomic policy. Effectuation concept serves as a theoretical basis. The concept was first introduced by S. Sarasvathy and has been used as an alternative or a complementary instrument for business construction. The authors transfer both the effectuation concept and causation one at the macro level by the adoption of qualitative type of methodology - case study at country’s level. Five principles of effectuation are described in brief and applied in parallel to the Chinese government macroeconomic policy in the period of rapid changes (starting in 1978 and to the end of XX century). For further support of conclusions, the article presents a microeconomic analysis of both concepts on the example of China: we tested the features of traditional Chinese management at the organization level on their compliance with effectuation and/or causation principles. Our main conclusion stands to support the one by Sarasvathy et al. meaning that the most effect (at the country’s level in our case) may be achieved solely by a complementary application of effectuation and causation. Reasonable integration of causation and effectuation principles promotes successful micro- and macroeconomic results. The case of China also serves to prove the possibility for effective management strategies on macro- and micro-levels emerging out of conflicting concepts and based on rather conservative cultural issues. The conclusions and results of this research may be used for state macroeconomic policy construction if certain conditions are satisfied.